Friction material and friction body for phase change heat storage composite brake pad and preparation method of friction material and friction body

By absorbing heat at high temperatures and the lubrication effect of graphene and graphite, the friction coefficient instability and wear increase caused by the increase in brake pad temperature is solved, and the low friction coefficient, low wear and high thermal stability is achieved, which extends the The service life of the brake pads.

CN119244671APending Publication Date: 2025-01-03YANCHENG INST OF TECH +1
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411368931.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When cars and trains drive at high speed or continuously braking down long slopes, the temperature of the brake pads rises sharply, resulting in unstable friction coefficient and increased wear, which makes it easy to cause braking failure.

Method used

The friction material for phase-change heat storage composite brake pads using Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder is used to absorb heat by reverse phase change at high temperature to reduce the temperature increase speed of the brake pads. Graphene and graphite are used as lubricating materials to stabilize the friction coefficient and improve thermal stability.

Benefits of technology

It achieves low friction coefficient and low wear during high-speed driving and continuous downhill slopes, extends the service life of the brake pads, and improves braking stability and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119244671A_ABST
    Figure CN119244671A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of application of brake materials for brake pads, and particularly discloses a friction material for a phase change heat storage composite brake pad, which comprises Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of (40-60): (10-25): (0.1-1.5): (10-30): (0.5-1.5): (4-6). The friction material for the brake pad has the beneficial effects that the prepared friction material for the brake pad is low in friction coefficient, good in wear resistance and good in heat fading resistance, and the service life is prolonged; cu is used as a matrix, and Cr and V are used as reinforced matrix components, so that the material plays an important role in the overall strength and wear resistance of the material for the brake pad; the CuAlMn particles are adopted, so that unstable friction coefficient and brake failure caused by over-high temperature of the friction material for the brake pad under the high-temperature condition are effectively relieved; graphene and graphite are used as lubricating materials, so that the friction coefficient is effectively reduced and stabilized, and the thermal stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brake material application for brake pads, and specifically relates to a friction material for a phase-change heat storage composite brake pad, a friction body and a preparation method thereof. Background Art

[0002] With the rapid development of global industry, people have higher and higher requirements for the safety, reliability and comfort of automobiles and high-speed trains. As an important guarantee for the safety of automobiles and trains, the performance and safety of the brake system have received extensive attention. Brake pads are the most critical components in the brake system. Therefore, the performance requirements for friction materials used in brake pads are also getting higher and higher, and it is necessary to continuously develop new friction materials for brake pads to meet market demand.

[0003] When a car or train is driving at high speed or braking continuously down a long slope, the brake pads and brake discs will be in contact for a long time, causing the temperature of the brake pads to rise sharply, making the friction coefficient unstable and the wear increased, causing brake failure and easily causing traffic accidents.

[0004] Therefore, there is an urgent need to develop a friction material for brake pads that is resistant to high temperatures and has low friction and wear, that is, it can maintain a low friction coefficient and excellent braking performance during high-speed driving and continuous descent of long slopes, and the wear will not increase.

[0005] Based on the above problems, the present invention provides a friction material for a phase-change heat storage composite brake pad, a friction body and a preparation method thereof. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a phase change heat storage composite brake pad friction material, friction body and preparation method thereof, preferably select each component and optimize process parameters, the friction material for brake pad prepared has a low friction coefficient, good wear resistance, good thermal decay resistance, and increased service life.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0008] The first aspect of the present invention provides a friction material for a phase-change heat storage composite brake pad, comprising Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6;

[0009] The Cu is used as the matrix, and Cr and V are components that strengthen the matrix, which play an important role in the overall strength and wear resistance of the brake pad material.

[0010] The CuAlMn particles utilize shape memory alloys to cause a reverse martensitic phase transformation during the temperature rise of the brake pads when the car or train is running at high speed or when braking continuously down a long slope. The transformation of martensite to austenite can absorb heat, so that during high-speed driving or when braking continuously down a long slope, the temperature rise of the brake pads is slowed down or stopped, and the friction coefficient is stable, the wear is reduced, and the braking is stable.

[0011] The use of graphene and graphite as lubricating materials effectively reduces and stabilizes the friction coefficient and improves thermal stability.

[0012] A second aspect of the present invention provides a method for preparing a friction material for a phase-change heat storage composite brake pad, the method comprising the following steps:

[0013] S1, mixing, putting Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder into a planetary ball mill according to a mass ratio of 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6 for wet mixing to prepare a uniform mixed powder;

[0014] S2. Put the mixed powder into a graphite mold, perform electric field assisted DC rapid hot pressing sintering on the mixed powder in a vacuum environment, and complete it under pressurized and heat-insulating conditions.

[0015] In the present technical solution, preferably, the particle sizes of Cu powder, Cr powder, V powder, CuAlMn particles and graphite powder are 325-375 mesh respectively, and the particle size of graphene powder is 500-550 mesh.

[0016] In the present technical scheme, preferably, the uniform mixing method in S1 is: adding anhydrous ethanol to wet mix Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6 on a planetary ball mill, the mixing time is 8 hours, the ball-to-material mass ratio is 5:1, the balls are zirconia balls, wherein the volume ratio of anhydrous ethanol to the ball material is 3:2, and the mixed powder is placed in an oven for drying at a drying temperature of 60°C until the powder is completely dry.

[0017] In the present technical solution, preferably, CuAlMn shape memory alloy particles are used in S1. During high-speed or long-term braking, the temperature of the brake pad rises sharply, and the CuAlMn shape memory alloy particles absorb heat during the phase change process, which slows down the temperature rise of the brake pad. After the braking process is completed, the CuAlMn shape memory alloy particles recover from the phase change and release the absorbed heat, thereby ensuring the braking stability during high-speed driving or long-term braking and improving driving safety.

[0018] In this technical solution, preferably, vacuum treatment is performed in the furnace before sintering, and the vacuum degree is maintained for 10 -1 MPa.

[0019] In the present technical solution, the sintering applied pressure is preferably maintained at 30-50 MPa.

[0020] In the present technical solution, the sintering temperature is preferably 900-1000°C.

[0021] In the present technical solution, the sintering heating rate is preferably 100-300°C / min.

[0022] In the present technical solution, the preferred holding time is 10-20 minutes.

[0023] A third aspect of the present invention provides a friction body, which is prepared by using the above-mentioned friction material for phase change heat storage composite brake pads and utilizing the above-mentioned preparation method.

[0024] Compared with the prior art, the friction material for a phase-change heat storage composite brake pad, the friction body and the preparation method thereof of the present invention have the following beneficial effects:

[0025] The present invention makes full use of the fact that shape memory alloys absorb heat during phase change. After the braking process is over, the shape memory alloy particles recover their phase change and release the absorbed heat, which can effectively improve the braking stability and friction coefficient during high-speed driving or continuous descent of long slopes, reduce the wear rate, and extend the service life.

[0026] The present invention adopts the above-mentioned component ratio and process parameters to produce a friction material for brake pads, which has a low friction coefficient, good wear resistance, good heat decay resistance, and increased service life;

[0027] The present invention uses Cu as the matrix, and Cr and V as the reinforcing matrix components, which play an important role in the overall strength and wear resistance of the brake pad material;

[0028] The present invention uses CuAlMn particles to utilize shape memory alloys. When a car or train is running at high speed or braking continuously down a long slope, the temperature of the brake pad is increased by a martensitic reverse phase transformation. The transformation of martensite to austenite can absorb heat, so that during high-speed driving or continuous braking down a long slope, the temperature rise rate of the brake pad is slowed down or stopped, and the friction coefficient is stable, the wear amount is reduced, and the braking is stable.

[0029] The present invention adopts graphene and graphite as lubricating materials, which can effectively reduce and stabilize the friction coefficient and improve thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a SEM image of a friction material for a phase-change heat storage composite brake pad of the present invention. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] In the description of the present invention, it should be noted that the orientations or positional relationships indicated by the terms "top", "bottom", "one side", "the other side", "front", "back", "middle part", "inside", "top end", "bottom end", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0034] Embodiment 1 of the present invention proposes a friction material for a phase change heat storage composite brake pad, which uses Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder as preparation raw materials, wherein the purity of Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder are all greater than 99.9%, and the particle sizes are 325 mesh, 325 mesh, 325 mesh, 325 mesh, 500 mesh and 325 mesh, respectively.

[0035] The above-mentioned method for preparing a friction material for a phase change heat storage composite brake pad comprises the following steps:

[0036] S1. Mix Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 53.07:20:0.5:20:1:5.43.

[0037] The mixed powder was mixed in a planetary ball mill for 8 hours at a mixing speed of 260 rpm to obtain a uniformly mixed powder, wherein the grinding balls used in the ball mill were zirconia balls, the ball-to-material mass ratio was 5:1, and the volume ratio of anhydrous ethanol to the ball-to-material was 3:2.

[0038] Pour out the milled powder, clean the grinding balls and the milling jar with anhydrous ethanol to avoid powder loss. Put the beaker containing anhydrous ethanol and powder into a blast drying oven for blast drying at 60°C until the powder is completely dry and then take it out.

[0039] S2. Put the mixed powder into a graphite mold and use an electric field assisted DC rapid hot pressing sintering device (FHP-828) to sinter the friction material for brake pads. Before sintering, vacuum the cavity of the equipment to a vacuum degree of 10 -1 MPa, sintering temperature is 950℃, heating rate is 150℃ / min, pressure is 40MPa, and holding time is 15min.

[0040] Embodiment 2 of the present invention proposes a friction material for a phase change heat storage composite brake pad, which uses Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder as preparation raw materials, wherein the purity of Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder are all greater than 99.9%, and the particle sizes are 350 mesh, 350 mesh, 350 mesh, 350 mesh, 525 mesh and 350 mesh, respectively.

[0041] The above-mentioned method for preparing a friction material for a phase change heat storage composite brake pad comprises the following steps:

[0042] S1. Mix Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 55.2:18:1.2:25:0.8:5.8.

[0043] The mixed powder was mixed in a planetary ball mill for 8 hours at a mixing speed of 260 rpm to obtain a uniformly mixed powder, wherein the grinding balls used in the ball mill were zirconia balls, the ball-to-material mass ratio was 5:1, and the volume ratio of anhydrous ethanol to the ball-to-material was 3:2.

[0044] Pour out the milled powder, clean the grinding balls and the milling jar with anhydrous ethanol to avoid powder loss. Put the beaker containing anhydrous ethanol and powder into a blast drying oven for blast drying at 60°C until the powder is completely dry and then take it out.

[0045] S2. Put the mixed powder into a graphite mold and use an electric field assisted DC rapid hot pressing sintering device (FHP-828) to sinter the friction material for brake pads. Before sintering, vacuum the cavity of the equipment to a vacuum degree of 10 -1 MPa, sintering temperature is 980℃, heating rate is 180℃ / min, pressure is 40MPa, and holding time is 18min.

[0046] Embodiment 3 of the present invention proposes a friction material for a phase change heat storage composite brake pad, which uses Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder as preparation raw materials, wherein the purity of Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder are all greater than 99.9%, and the particle sizes are 375 mesh, 375 mesh, 375 mesh, 375 mesh, 550 mesh and 375 mesh, respectively.

[0047] The above-mentioned method for preparing a friction material for a phase change heat storage composite brake pad comprises the following steps:

[0048] S1. Mix Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 55.8:22:1.35:28:1.3:6.

[0049] The mixed powder was mixed in a planetary ball mill for 8 hours at a mixing speed of 260 rpm to obtain a uniformly mixed powder, wherein the grinding balls used in the ball mill were zirconia balls, the ball-to-material mass ratio was 5:1, and the volume ratio of anhydrous ethanol to the ball-to-material was 3:2.

[0050] Pour out the milled powder, clean the grinding balls and the milling jar with anhydrous ethanol to avoid powder loss. Put the beaker containing anhydrous ethanol and powder into a blast drying oven for blast drying at 60°C until the powder is completely dry and then take it out.

[0051] S2. Put the mixed powder into a graphite mold and use an electric field assisted DC rapid hot pressing sintering device (FHP-828) to sinter the friction material for brake pads. Before sintering, vacuum the cavity of the equipment to a vacuum degree of 10 -1 MPa, sintering temperature is 1000℃, heating rate is 200℃ / min, pressure is 40MPa, and holding time is 20min.

[0052] The friction body of the present invention is prepared by the above-mentioned friction material for brake pads using the above-mentioned method, which has low energy consumption and is green and environmentally friendly. The prepared new friction material and friction body for brake pads have low friction coefficient, good wear resistance, good heat decay resistance, and increased service life.

[0053] In the method for preparing the friction material for brake pads proposed in the embodiment of the present invention, the optimized ratio of each component and the process parameters are adopted to prepare the friction material for brake pads with uniform microstructure. Figure 1 shown.

[0054] The hardness, friction coefficient and wear rate of the phase change heat storage composite brake pad friction material prepared by the above specific implementation method are tested to test the hardness difference of the brake pad friction material made of the same material, different component ratios and process parameters, and the friction coefficient and wear rate during operation, as shown in the following table:

[0055]

[0056] Example 1 The hardness of the friction material for the brake pad is 105HV1 / 15, the friction coefficient is 0.28, and the wear rate is 0.12mm 3 ·N -1 ·m -1 The hardness of the friction material for the brake pad measured in Example 2 is 116HV1 / 15, the friction coefficient is 0.33, and the wear rate is 0.23mm 3 ·N -1 ·m -1 The hardness of the friction material for the brake pad measured in Example 3 is 145HV1 / 15, the friction coefficient is 0.31, and the wear rate is 0.18mm 3 ·N -1 ·m -1 .

[0057] Through the above tests, the present invention can effectively improve the hardness of the friction material for the brake pad, and has a low friction coefficient and low wear, and can effectively extend the service life of the brake pad.

[0058] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0059] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A friction material for a phase-change heat storage composite brake pad, characterized in that: It includes Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder, and the mass ratio is 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6; The Cu is used as the matrix, and Cr and V are components that strengthen the matrix, which play an important role in the overall strength and wear resistance of the brake pad material. The CuAlMn particles utilize the fact that when a car or train is running at high speed or braking continuously down a long slope, the shape memory alloy undergoes a reverse martensitic phase transformation during the temperature rise of the brake pad. The transformation of martensite to austenite can absorb heat, so that during high-speed driving or continuous braking down a long slope, the temperature rise rate of the brake pad is slowed down or stopped, and the friction coefficient is stable, the wear is reduced, and the braking is stable. The use of graphene and graphite as lubricating materials effectively reduces and stabilizes the friction coefficient and improves thermal stability.

2. The method for preparing a friction material for a phase-change heat storage composite brake pad according to claim 1, characterized in that: The following steps are included: S1. Put Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder into a planetary ball mill according to a mass ratio of 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6 for wet mixing to prepare a uniform mixed powder; S2. Put the mixed powder into a graphite mold, apply pressure to maintain at 30-50MPa in a vacuum environment, keep the temperature at 900-1000°C, and keep the temperature for 10-20min. Use electric field assisted DC rapid hot pressing sintering to sinter the mixed powder.

3. The method for preparing a friction material for a phase-change heat storage composite brake pad according to claim 2, characterized in that: The particle sizes of the Cu powder, Cr powder, V powder, CuAlMn particles and graphite powder are 325-375 meshes respectively, and the particle size of the graphene powder is 500-550 meshes.

4. The method for preparing a friction material for a phase-change heat storage composite brake pad according to claim 2, characterized in that: The uniform mixing method in S1 is: adding anhydrous ethanol to wet mix Cu powder, Cr powder, V powder, CuAlMn particles, graphene powder and graphite powder in a mass ratio of 40-60:10-25:0.1-1.5:10-30:0.5-1.5:4-6 on a planetary ball mill, the mixing time is 8 hours, the ball material mass ratio is 5:1, the ball is a zirconia ball, wherein the volume ratio of anhydrous ethanol to the ball material is 3:2, and the mixed powder is placed in an oven for drying at a drying temperature of 60°C until the powder is completely dry.

5. The method for preparing a friction material for a phase-change heat storage composite brake pad according to claim 2, characterized in that: The S1 adopts CuAlMn shape memory alloy particles. During high-speed or long-term braking, the temperature of the brake pad rises sharply, and the CuAlMn shape memory alloy particles absorb heat during the phase change process, so that the temperature rise rate of the brake pad is slowed down. After the braking process is completed, the CuAlMn shape memory alloy particles recover from the phase change and release the absorbed heat, thereby ensuring the braking stability during high-speed driving or long-term braking and improving driving safety.

6. The method for preparing a friction material for a phase-change heat storage composite brake pad according to claim 2, characterized in that: In the process of electric field assisted DC rapid hot pressing sintering and maintaining pressure and heat preservation in S2: vacuum treatment is carried out in the furnace, and the vacuum degree is 10 -1 MPa, the applied pressure is maintained at 30-50MPa, the sintering temperature is 900-1000℃, the sintering heating rate is 100-300℃ / min, and the holding time is 10-20min.

7. A friction body, characterized in that: The phase change heat storage composite brake pad friction material according to claim 1 is prepared by the preparation method according to claims 2-6.

Citation Information

Cited By

  • Phase change material for aircraft brake disc

    CN120192747A

  • Design method of drum brake with temperature regulation and pressure compensation functions

    CN120332370A

  • Wind power electromagnetic brake friction material and preparation method thereof

    CN120736827A

  • A wind power electromagnetic brake friction material and a preparation method thereof

    CN120736827B